On smoothing problems with one additional equality condition - Asmuss, Svetlana; Budkina, Natalia (Mathematical Modelling and Analysis, 2009)
Two problems of approximation in Hilbert spaces are considered with one additional equality condition: the smoothing problem with a weight and the smoothing problem with an obstacle. This condition is a generalization of the equality, which appears in the problem of approximation of a histogram in a natural way. We characterize the solutions of these smoothing problems and investigate the connection between them.First published online: 14 Oct 2010